Everything you need to know about science homework - Zeman, Anne, 1951-; Kelly, Kate. (New York : Scholastic Reference, 1997)
Provides fourth to sixth grade students and parents with information they need to complete science assignments. Includes information such as: the animal and plant kingdom, vertebrates and invertebrates, photosynthesis, food chains and food webs, biomes, environmental issues, how the Earth was formed, and much more.
What's life all about? -- The animal kingdom -- The plant kingdom -- Ecology and the landscapes of life -- Planet Earth -- Outer space -- The physical world.
"A desk reference for students and parents"--Cover.
"An Irving Place Press book".
"In collaboration with UFT Dial-a-teacher"--Cover.
Includes index.
5.5
3-6
Keywords: Homework -- Juvenile literature; Science -- Study and teaching -- Juvenile literature; Homework; Science; Homework; Science -- Study and teaching; Study skills